Why is Productivity Growth in the Euro Area so Sluggish? - Estevão, Marcello M. (International Monetary Fund, 2004)
Slow productivity growth has plagued the euro area since the mid-1990s. That is particularly striking in view of the large productivity gains in the United States during the same period. This paper shows that the deceleration in labor productivity in the euro area was caused by structural changes in wage formation that have affected the relative price of labor, increased the labor intensity of growth and, thus, reduced the rate of capital deepening. Technological shocks seem to have played a minor role in explaining slower productivity growth in the euro area. In addition, a surge in capital deepening and, mainly, TFP growth in key service industries in the United States explain a large part of the productivity growth gap between the two regions in the second half of the 1990s